Ketamine and other glutamate receptor modulators for depression in bipolar disorder in adults - McCloud, T; Caddy, C; Jochim, J; Rendell, J; Diamond, P; Shuttleworth, C; Brett, D; Amit, B; McShane, R; Hamadi, L; Hawton, K; Cipriani, A (Royal College of Psychiatrists, 2016)
There is emerging evidence that glutamatergic system dysfunction might play an important role in the pathophysiology of bipolar depression. This review focuses on the use of glutamate receptor modulators for depression in bipolar disorder. This review is an abridged version of a Cochrane review previously published in the Cochrane Database of Systematic Reviews, 2015, Sep 29, Issue 9, CD011611